Alterations to the bending mechanical properties of Pinus sylvestris timber according to flatwise and edgewise directions and knot position in the cross-section - Fernández-Serrano, Álvaro; Villasante, Antonio (Maderas. Ciencia y Tecnología, 2024)
Given the heterogeneity of the material, the behaviour of a timber beam may differ depending on which of its sides is subjected to tension and which one is subjected to compression. An analysis is undertaken in the present work of the behaviour in non-destructive bending tests on the four sides of 57 samples of Pinus sylvestris (scots pine) of structural size (2000 × 100 × 70 mm3). A study is additionally performed of the influence of the size and position of knots in the cross-section. The modulus of elasticity in flatwise direction was found to be 3 % higher than in edgewise direction. This difference could be attributable to the shear effect. While the introduction of knottiness variables did not improve modulus of elasticity prediction, it did decrease the error in the prediction of the modulus of rupture. The margin knot area ratio corresponding to the outer eighth of the cross-section’s width occupied by knots was the knottiness variable with the lowest error in modulus of rupture prediction.